Factors influencing donor and recipient decision making in adult‐to‐adult living donor liver transplantation: a survey of a non‐transplant population. Issue 3 (11th September 2014) - Lansom, Joshua D.; Rowe, Simon; Sandroussi, Charbel; Harrison, James D.; Solomon, Michael; McCaughan, Geoffrey; Crawford, Michael
Abstract: Background: This study aimed to (i) investigate the factors that influence donor and recipient decision making in adult‐to‐adult living donor liver transplantation (AALDLT); (ii) quantify the level of risk that would be acceptable to potential donors; and (iii) determine from whom an individual would be willing to receive a donation. Methods: A self‐administered questionnaire using hypothetical scenarios centred on AALDLT was created and administered to participants recruited from the waiting room of an orthopaedic outpatient clinic at a teaching hospital in Sydney ( n = 105). The questionnaire asked participants to consider scenarios in which they either (i) were a potential donor for a family member or close friend or (ii) themselves required a liver transplant. Results: Ninety‐five (90%) participants expressed an in‐principal willingness to consider living organ donation. The factors most important in deciding to be living liver donors were the probability of a good outcome for the recipient, the likelihood of the potential recipient's survival until a deceased donor liver became available and the risk of donor death. Donor death was also rated as the least acceptable donor outcome. Participants expressed a willingness to receive a donation from all proposed donor groups equally. Conclusions: The acceptability of hypothetical living organ donation was very high in the population group studied. Participants were also willing to accept significantly higher risks of complications from organ donation than they would actually be exposed to. Clinicians should feel encouraged to discuss the risks and benefits of living donation frankly with patients and their families.